Community Driven Development and Structural Disadvantage: Interrogating the Social Turn in Development Programming in Indonesia. Issue 12 (2nd December 2017) - McCARTHY, J.F.; Steenbergen, D.J.; Warren, C.; Acciaioli, G.; Baker, G.; Lucas, A.; Rambe, V.
Abstract : Community-driven development (CDD) programmes have emerged on a large scale in the Global South following research and policy work regarding social capital, capabilities and empowerment. This paper analyses one of the largest international examples of the 'social' turn, examining the effects of the CDD approach in governmental, structural and relational terms. While the CDD approach successfully generated new political rationalities and governmental technologies, the ability of development programming driven by social capital concepts to empower marginalised sections of society remains in question. The ambiguities associated with CDD outcomes indicate the contradictions at the heart of social capital debate.